2008
DOI: 10.1161/circresaha.108.178475
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 From Transplanted Bone Marrow Mononuclear Cells Contributes to Cardiac Protection After Myocardial Infarction

Abstract: Abstract-Bone marrow mononuclear cells (BM-MNCs) have successfully been used as a therapy for the improvement of left ventricular (LV) function after myocardial infarction (MI). It has been suggested that paracrine factors from BM-MNCs may be a key mechanism mediating cardiac protection. We previously performed microarray analysis and found that the pleiotropic cytokine interleukin (IL)-10 was highly upregulated in human progenitor cells in comparison with adult endothelial cells and CD14 ϩ cells. Moreover, BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 47 publications
(36 reference statements)
8
95
1
3
Order By: Relevance
“…31 Moreover, the previous study by Burchfield et al showed that IL-10 from transplanted bone marrow mononuclear cells contributed to cardiac protection after MI in association with a decrease in T lymphocyte accumulation, reactive hypertrophy, and myocardial collagen deposition. 32 However, in the present study, zymographic MMP-9 level was not affected by αGC, which was consistent with the infiltration of lymphocyte observed by immunohistochemical staining for CD3 ( Figure 5). We also measured the protein levels of HuR/MMP-9 or STAT3 in the noninfarcted LV.…”
Section: Possible Mechanisms Of Il-10 For the Attenuation Of LV Remodsupporting
confidence: 91%
“…31 Moreover, the previous study by Burchfield et al showed that IL-10 from transplanted bone marrow mononuclear cells contributed to cardiac protection after MI in association with a decrease in T lymphocyte accumulation, reactive hypertrophy, and myocardial collagen deposition. 32 However, in the present study, zymographic MMP-9 level was not affected by αGC, which was consistent with the infiltration of lymphocyte observed by immunohistochemical staining for CD3 ( Figure 5). We also measured the protein levels of HuR/MMP-9 or STAT3 in the noninfarcted LV.…”
Section: Possible Mechanisms Of Il-10 For the Attenuation Of LV Remodsupporting
confidence: 91%
“…Finally, the loss of antiinflammatory responses may also play a role in increasing pulmonary inflammation and airway hyperresponsiveness in SCD. For example, although IL-10, which decreases inflammation and prevents abnormal collagen deposition (24,25), was similar in Non-Sen chi-HbA and chi-SCD mice, after OVA-sensitization, OVASen chi-HbA mice were able to increase IL-10 production, but OVA-Sen chi-SCD mice were not. Failure to mount an antiinflammatory IL-10 response in the presence of robust increases in IL-5 and MCP-1 may account, at least in part, for the enhanced eosinophil recruitment and collagen deposition that occurred in the perialveolar and perivascular regions in the OVA-Sen chi-SCD mice.…”
Section: Discussionmentioning
confidence: 97%
“…Delivery of BMSC to ischemic cardiac tissue has led to a significant increase in the concentration of IL-10, interleukin-1 (IL-1 ), tumor necrosis factor-(TNF-) and other cytokines in the cardiac tissue, which contributed to neovascularization and reduction of infarct size (Kamihata et al, 2001;Burchfield et al, 2008;Gnecchi et al, 2005;Mirotsou et al, 2011). Condition media in which BMSC were exposed to hypoxia proved to be cytoprotective to cardiomyocytes and was able to reduce infarct size (Gnecchi et al, 2006).…”
Section: Paracrine Effectmentioning
confidence: 99%